DNA polimerase beta: uma proteína envolvida na replicação e reparo do DNA mitocondrial emTrypanosoma cruzi - Bruno Luiz Fonseca Schamber Reis (2010)
During its life cycle, the causative agent of Chagas Disease Trypanosoma cruzi must deal with the deleterious action of reactive oxygen species (ROS) on DNA, mainly 7,8-dihydro-8-oxoguanine (8oxoG). If unrepaired, 8oxoG can lead to transversions during cell division. In mammals, DNA polymerase beta (pol) is strictly involved in base excision repair (BER) of oxidative damage. However its biological function in T.cruzi is still uncertain. Immunofluorescent analysis revealed that pol is localized on antipodal sites of kinetoplast (kDNA) of replicative epimastigotes and amastigotes forms. Nevertheless, the polymerase was seen dispersed in non-replicative trypomastigote forms inside the mitochondrion matrix, suggesting its participation in kDNA replication. In addition, we verify that pol is strictly localized in kDNA antipodal sites between G1/S and early G2 phase of replicative epimastigotes. Clonesoverexpressing pol presented increased survival after treatment with H2O2 and benznidazol compared to control. However this resistance is lost after treating cells with methoxiamine, a potent BER inhibitor. We also verified that the overexpressing clones showed a reduced level of detected 8oxoG in kinetoplast when compared to control. Curiously, a possible DNA repair focus of pol was identified in the vicinity ofkinetoplast of epimastigotes wild type CL Brener cells after H2O2 treatment. We believe that this focus is a DNA repair focus probably mounted in kinetoflagellar zone after oxidative damage to kDNA. Taken together the experimental data obtained suggest participation of pol in DNA replication and repair of oxidative damages in kDNA of T. cruzi.